2016
DOI: 10.1007/s10823-016-9280-6
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Widowhood on Parent–Child Relationships in Korea: Do Parents’ Filial Expectations and Geographic Proximity to Children Matter?

Abstract: Although previous research based on data from the U.S. suggests that parents' widowhood is associated with increased emotional support from children, little is known about the impact of late-life widowhood on intergenerational relationships in other cultures. Using data of Korean older adults, this paper examined: (1) the effect of widowhood on both positive and negative aspects of parent-child relationships and (2) whether these effects are moderated by older adults' expectations about children's filial respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…The results of this study indicate that both older Koreans and Korean-Americans still expect significant care from their adult children. While these results are similar to those in most studies with Korean samples (e.g., Ha et al, 2016) and Chinese or other ethnic immigrant elderly (e.g., Laielaw et al, 2010;Luo & Zhan, 2012;Peek et al, 1998), a remarkable difference was found in an American study that used the EFR between groups (Lee et al, 1998). Although the overall level of filial piety was similar between the two samples, clearly a distinct difference between the two groups was regarding financial assistance.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…The results of this study indicate that both older Koreans and Korean-Americans still expect significant care from their adult children. While these results are similar to those in most studies with Korean samples (e.g., Ha et al, 2016) and Chinese or other ethnic immigrant elderly (e.g., Laielaw et al, 2010;Luo & Zhan, 2012;Peek et al, 1998), a remarkable difference was found in an American study that used the EFR between groups (Lee et al, 1998). Although the overall level of filial piety was similar between the two samples, clearly a distinct difference between the two groups was regarding financial assistance.…”
Section: Discussionsupporting
confidence: 85%
“…Accordingly, older adults would face the wide gap between what older adults expect from their children and the actual practice and behaviors of younger generations to fulfill these expectations. Thus, intergenerational ambivalence theory explains the coexistence of positive and negative sentiment in parent-child relations in the Korean family care system (Ha et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations